2017
DOI: 10.1039/c7pp00051k
|View full text |Cite
|
Sign up to set email alerts
|

Photophysicochemical characterization of mycosporine-like amino acids in micellar solutions

Abstract: The properties and photochemical and photophysical behavior of the mycosporine-like amino acids (MAAs) shinorine and porphyra-334 were experimentally evaluated in solutions of direct ionic micelles as simple biomimicking environments. The preferential partition of the natural molecules in the aqueous phase of sodium dodecyl sulfate (SDS) or cetyltrimethylammonium chloride (CTAC) micellar systems is confirmed. Although the proton dissociation of the carboxylic groups in the MAAs is slightly inhibited in CTAC so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 36 publications
4
12
0
Order By: Relevance
“…Indeed, the parameters in Table 1 account for relative decreases in the photodecomposition quantum yields by factors of two in water and of six in SDS solution. Thus, the effects in micellar media for SDME are in line with the results for shinorine and porphyra-334: the stronger coulombic attractions with the micellar surface, the better protection toward photodecomposition (18).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, the parameters in Table 1 account for relative decreases in the photodecomposition quantum yields by factors of two in water and of six in SDS solution. Thus, the effects in micellar media for SDME are in line with the results for shinorine and porphyra-334: the stronger coulombic attractions with the micellar surface, the better protection toward photodecomposition (18).…”
Section: Resultssupporting
confidence: 82%
“…Electrostatic interactions have been already invoked to account for the micellar effects in the photophysics of the MAAs shinorine and porphyra‐334 in SDS and CTAC solutions . The results of that previous study support the preferential solubilization of the MAAs in the aqueous phase outside the direct micelles and, due to the zwitterionic character of the natural compounds under physiologic pH, the possibility of columbic interactions with the charged heads of the surfactants.…”
Section: Resultsmentioning
confidence: 69%
“…Recently, Orallo et al [ 136 , 137 ] have performed studies on the MAAs shinorine, porphyra-334 and shinorine dimethyl ester in micellar solutions to elucidate the photochemistry and photophysics in a closer-to-real sunscreen formulation environment. They found that the fluorescence quantum yield and lifetime were increased in micelle solutions compared to aqueous solutions; however, the main deactivation process remained via non-radiative decay.…”
Section: Case Studiesmentioning
confidence: 99%
“…The authors attributed both properties to the electrostatic interactions between MAAs and micelles which hinder molecular movements. Overall, Orallo et al [ 136 , 137 ] demonstrated that MAAs in micellar solutions which mimic a closer-to-real environment, with regards to sunscreen formulation, still perform as efficient UV filters which is promising for commercial applications. However, the electrostatic interactions which influence the decay mechanisms must be taken into account.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation